Índices de estresse térmico e perfil metabólico nos períodos de transição e espera voluntária de vacas da raça girolando, criadas em clima tropical - Marins, Thiago Nogueira (2016)
Heat stress is one of the most important factors with negative impact on the animal productivity in tropical countries. This longitudinal study was designed to describe the physiological response and the metabolic profile of Girolando (Holsteins X Gir, 3/4, 5/8 and 7/8) cows raised in a tropical region during the transition and voluntary waiting period (VWP). Twenty cows were selected using the following criteria: well distributed black and white coat, parity between two and seven, milk yeld between 18 and 22 L / day. The temperature-humidity index (THI) and black globe temperature and humidity index (BGT) of the micro environment were measured daily. Cows were clinically evaluated and submitted to blood collection in intervals distributed between three weeks before parturition until 60 days after calving (12 evaluations / cow). Physical examination included rectal temperature (RT), heart and respiratory rate (HR and RR) measured in the morning (6-8h) and afternoon (14-16h). RT and RR were used to calculate the Benezra Comfort Index (BCI). Metabolic profile was assessed by measurement of glucose, non-esterified fatty acid (NEFA), βhydroxybutyrate (βHBA), triglycerides, cholesterol, HDL, total serum protein, albumin, immune globulin, urea, creatinine, AST, GGT, calcium, phosphorus and magnesium. From 8-16h, throughout all the evaluation period, the average values of THI ranged from 73.5 and 78.7 and BGHI between 81.8 and 88.2. The variables HR, RR, RT and BCI differ (P <0.05) between morning and afternoon throughout the study period. Means glucose concentrations were similar in antepartum, decreased on the day of calving, reaching the lowest concentration on the 5th day postpartum. NEFA’s highest value was found on the day of parturition, and decreased, while βHBA decreased until the week before calving and increased on the calving day and after. The concentrations of triglycerides decreased, but cholesterol and HDL increased from the calving day. Total protein concentrations and immunoglobulin decreased from the second antepartum week and increased from the 2nd day postpartum. Urea increased on the week close to calving, but creatinine decreased postpartum. AST and GGT reached the highest value in the beginning of the postpartum period. Ca and P showed lower values on the calving day and Mg decreased during the early postpartum period, returning to the previous levels on the 10th day postpartum. In conclusion, thermal conditions and physiological differences during transition and VWP influence the evaluation of physical and metabolic variables.